2020
DOI: 10.3389/fpls.2020.572199
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Microbiome in the Soil of an American Ginseng Continuous Plantation

Abstract: American ginseng is an important herbal medicinal crop in China. In recent years, there has been an increasing market demand for ginseng, but the production area has been shrinking due to problems associated with continuous monocropping. We analyzed the microbiome in bulk soils to assess whether and, if so, what changes in the bulk soil microbiome are associated with continuous American ginseng cropping. The alpha diversity of fungi and bacteria was significantly lower in the soils planted with American ginsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 40 publications
6
22
0
Order By: Relevance
“…Phenolic acids reduce the uniformity of fungi, which is beneficial to the enrichment of some fungi, but this is not beneficial for plants. Because most plant diseases are caused by fungi, the accumulation of rhizospheric fungi may exacerbate continuous cropping soil sickness ( Zhang et al, 2020 ). Beta-diversity analysis showed that phenolic acids could significantly change bacterial community structure.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids reduce the uniformity of fungi, which is beneficial to the enrichment of some fungi, but this is not beneficial for plants. Because most plant diseases are caused by fungi, the accumulation of rhizospheric fungi may exacerbate continuous cropping soil sickness ( Zhang et al, 2020 ). Beta-diversity analysis showed that phenolic acids could significantly change bacterial community structure.…”
Section: Discussionmentioning
confidence: 99%
“…Soil sickness affects both crop quality and yields when the same crop or its relative species are continuously grown in the same soil under a monocropping system ( Zhang et al, 2020b ). The rhizosphere microbiome acts as the first line of defense against soilborne pathogen infection and abiotic stress ( Bulgarelli et al, 2013 ; Mendes et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that long-term continuous cropping alters physical properties of the soil [12] and the soil microbial community structure, resulting in a diminished community of bene cial microorganism in soil, an increase in the pathogenic microorganisms, and a decline in the yield and quality of medicinal materials [13]. For example, the continuous planting of American ginseng [14] and Sophora avescens [15] not only weakened soil microbial diversity and amassed fungal root pathogens, but also changed soil physical properties, resulting in decreased crop yield and quality.…”
Section: Introductionmentioning
confidence: 99%